If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5tanx + -5 = 0 Reorder the terms: -5 + 5antx = 0 Solving -5 + 5antx = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + 5antx = 0 + 5 Combine like terms: -5 + 5 = 0 0 + 5antx = 0 + 5 5antx = 0 + 5 Combine like terms: 0 + 5 = 5 5antx = 5 Divide each side by '5ntx'. a = n-1t-1x-1 Simplifying a = n-1t-1x-1
| ax-2x=a^2-4 | | (x+2)(x+3)(x+4)(x+1)=24 | | 64x=0 | | 4a=3a-7 | | 28y-(5x-17y)= | | 11x-24-5x= | | 11x-24-5x=16x-24 | | 2x+86=50 | | 6x-5=-15(x+5) | | 28+8x=8x+27+2 | | -6(2t+9)=-42 | | 6p-4p=3p-4 | | A/25 | | 2x=6+26 | | 3y-5*4=2y+1 | | 4y+16x=-28 | | 5(f-3)=20 | | (X-3)/4=1/2 | | (9*x)+(5*y)=28 | | 3.4+0.2d=1.4 | | 2mx+(m-2)y-2=0 | | 3.4+02d=1.4 | | 2a-7=6 | | 125/x=15 | | 4/9d=-2/9 | | (x-18)*6=48 | | tan=x | | 7/4*3/2 | | 0.5(4x+18)=-1.5(5x)-2(3x+4.5) | | t-34=61/4 | | 4x-12=3x+7 | | -32-28x=-10-6x |